Pupillary Dilation in Clinical Practice - Trevino, R.C. (Canadian Journal of Optometry, 2026)
Pupillary dilation facilitates examination of the ocular fundusand media. A dilated pupil not only pennits ophthalmoscopic examination of the otherwise inaccessible regions of the peripheral fundus, but it also allows utilization of instruments which offer steropsis. An example of such an instrument is the binocular indirect ophthalmoscope. With this instrument the entire fundus from posterior pole to pars plana may be readily examined. The nonmydriatic adjustment available on some binocular indirect ophthaJmoscopes brings the observation and illumination beams very close together to allow viewing through smaller pupils. This arrangement increases reflections, reduces stereopsis, and ophthalmoscopy is generally limited to the posterior funds. As a rule, the larger the pupil the easier it becomes to view the peripheral fundus.